2008
DOI: 10.1016/j.pscychresns.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI study of the interface between affective and cognitive neural circuitry in pediatric bipolar disorder

Abstract: The pathophysiology of pediatric bipolar disorder (PBD) impacts both affective and cognitive brain systems. Understanding disturbances in the neural circuits subserving these abilities is critical for characterizing developmental aberrations associated with the disorder and developing improved treatments. Our objective is to use functional neuroimaging with pediatric bipolar disorder patients employing a task that probes the functional integrity of attentional control and affect processing. Ten euthymic unmedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
155
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(178 citation statements)
references
References 62 publications
21
155
2
Order By: Relevance
“…This favours the hypothesis that in paediatric BD there is both an enhanced reactivity in the limbic system and a reduced capacity of regulating this response by PFC when negative emotional stimuli are presented. The same pattern of activation was not found in paediatric BD for the positive words and it was not present for the healthy controls, neither in the positive condition nor in the negative condition (Pavuluri et al 2008).…”
supporting
confidence: 66%
“…This favours the hypothesis that in paediatric BD there is both an enhanced reactivity in the limbic system and a reduced capacity of regulating this response by PFC when negative emotional stimuli are presented. The same pattern of activation was not found in paediatric BD for the positive words and it was not present for the healthy controls, neither in the positive condition nor in the negative condition (Pavuluri et al 2008).…”
supporting
confidence: 66%
“…Other studies using emotional stimuli have revealed a pattern of increased subcortical striatal and limbic activation alongside reduced prefrontal cortex activity in BD (see Green et al 2007). This pattern of activity is also evident in pediatric cases of BD (Dickstein et al 2007 ;Pavuluri et al 2008). In schizophrenia, there is a contrasting pattern of decreased limbic activation and hyperfrontality during emotion processing tasks (e.g.…”
Section: Functional Mri (Fmri)mentioning
confidence: 76%
“…We have previously shown that in healthy individuals SCWT performance correlates positively with grey matter volume in the ACC and in the dorsal and ventral PFC; however these structure-function relationships are absent in BD patients (Haldane et al, 2008). Additionally, decreased activation in the VLPFC during the SCWT has been consistently reported in functional magnetic resonance imaging (fMRI) studies of adult (Blumberg et al, 2003;Gruber et al, 2004;Kronhaus et al, 2006;Lagopoulos and Malhi, 2007;Roth et al, 2006) as well as adolescent BD patients (Pavuluri et al, 2008). Therefore current evidence suggests that syndromal expression of BD is reliably associated with dysfunction within brain regions involved in inhibitory control (Aron et al, 2004;Nee et al, 2007;Rubia et al, 2001).…”
Section: Introductionmentioning
confidence: 93%